Secretin Modulates the Postnatal Development of Mouse Cerebellar Cortex Via PKA- and ERK-dependent Pathways - Wang, Lei; Zhang, Li; Chow, Billy K. C. (Frontiers in Cellular Neuroscience, 2017)
Postnatal development of the cerebellum is critical for its intact function such as motor coordination and has been implicated in the pathogenesis of psychiatric disorders. We previously reported that deprivation of secretin (SCT) from cerebellar Purkinje neurons impaired motor coordination and motor learning function, while leaving the potential role of SCT in cerebellar development to be determined. SCT and its receptor (SCTR) were constitutively expressed in the postnatal cerebellum in a temporal and cell-specific manner. Using a SCT knockout mouse model, we provided direct evidence showing altered developmental patterns of Purkinje cells (PCs) and granular cells (GCs). SCT deprivation reduced the PC density, impaired the PC dendritic formation, induced accelerated GC migration and potentiated cerebellar apoptosis. Furthermore, our results indicated the involvement of protein kinase A (PKA) and extracellular signal regulated kinase (ERK) signaling pathways in SCT-mediated protective effects against neuronal apoptosis. Results of this study illustrated a novel function of SCT in the postnatal development of cerebellum, emphasizing the necessary role of SCT in cerebellar-related functions.